Mathematical Model, Stability Analysis and Numerical Simulations for The Spread of Malaria Disease in Yogyakarta City, Indonesia - Prihantini Prihantini (Jurnal Fourier, 2021)
Indonesia is a country with frequent malaria cases. Therefore, a mathematical model is needed to model the distribution of malaria. The purpose of this study is to create a model with susceptible, infected, dormant and recovered compartments and to see the results of the simulation performed using maple 18 software. From the simulation results, it can be concluded that there is a decrease in the infected population and an increase in the recovered population over time.